Should lymph nodes from colorectal cancer resection specimens be processed in their entirety?. Issue 2 (19th October 2011) - Ervine, Aaron; Houghton, Joe; Park, Richard
Abstract : Aims: To quantify the benefit of processing each lymph node in its entirety in colorectal cancer specimens. Methods: 391 consecutive cases were examined retrospectively to assess how often cases were upstaged to node positive disease by examining each node in its entirety. Results: 7 out of 391 patients were upstaged by this method. However, of those patients, approximately three could have been detected by chance. Therefore, approximately 1% of cases were correctly upstaged. However, six of these seven patients also had at least one additional adverse prognostic factor, and would otherwise have been considered high risk Dukes' B cases. Conclusions: Processing all slices of each lymph node significantly increases laboratory workload and is of minimal clinical benefit.